The Impact of Sustainability Information Disclosure and Environmental, Social, and Governance (ESG) Performance on Sustainability Risks in Banking Companies Listed on the Indonesia Stock Exchange (IDX) in 2020-2023 - Elisa Khansa Thohira; RM. Rum Hendarmin; Reny Aziatul Pebriani (Economics and Digital Business Review, 2026)
This research analyzes the influence of Sustainability Information Disclosure and Environmental, Social, and Governance (ESG) Performance on Sustainability Risk in banking companies in Indonesia. This research uses secondary data from annual reports and sustainability reports of banks listed on the Indonesia Stock Exchange for the 2020–2023 period. The sampling technique used purposive sampling, so that 17 companies were obtained with a total of 68 observations. The sustainability disclosure variable is measured using the ESG Disclosure Index, ESG performance is measured through the E–S–G composite score, and sustainability risk is calculated using the Z Score Normalization method. Data analysis was carried out using multiple linear regression. The research results show that sustainability disclosure and ESG performance have a significant effect on sustainability risk, both partially and simultaneously. These findings indicate that improving the quality of sustainability disclosures and ESG performance contributes to reducing sustainability risks in the Indonesian banking sector.